Tantangan Persebaran Perbankan Syariah di Indonesia Akibat Kurangnya Kesadaran Masyarakat - Faiqotul Himmah; Fauzatul Laily Nisa (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
Islamic banking is a type of banking that operates based on Islamic sharia rules, which integrates legal rules in the Koran and Hadith in financial services without the use of interest or risky trading. This research aims to determine the quality of public awareness about sharia banking, the rationale behind it, the difficulties faced, and the level of awareness of the Indonesian people. The main subject of this research is the influence of low public awareness on the spread of sharia banking, using secondary data and qualitative descriptive methods. In addition, this research examines the initiatives taken to increase awareness of Islamic banking. A comprehensive analysis was carried out to present a general picture of the state of sharia banking in Indonesia, with the aim of producing comprehensive insights that support efforts to increase public knowledge and involvement in the sector.